Pengaruh Kontrol Diri, Cyberloafing, dan Motivasi Kerja terhadap Kinerja Karyawan Gen Z di Kota Yogyakarta - Vanderson, Vanderson; Kirana, Kusuma Chandra; Septyarini, Epsilandri (J-MAS (Jurnal Manajemen dan Sains), 2024)
This study aims to investigate the influence of self-control, cyberloafing, and work motivation on the performance of Gen Z employees in Yogyakarta City. It is a quantitative research study. The population studied encompasses all Gen Z employees working in the Yogyakarta region, born between 1996 and 2012. The researcher employed a questionnaire to gather data, utilizing a Likert scale for measurement. The study targeted employees aged 18-25 or Gen Z individuals working in Yogyakarta. Data analysis was conducted using Multiple Linear Regression. The findings indicate that self-control does not significantly affect the performance of Gen Z employees in Yogyakarta City, as evidenced by a significance value of 0.917 > 0.05. Similarly, cyberloafing does not significantly impact the performance of Gen Z employees in Yogyakarta City, supported by a significance value of 0.878 > 0.05. However, work motivation shows a significant positive influence on the performance of Gen Z employees in Yogyakarta City, as supported by a significance value of 0.016 < 0.05.